ANALISIS FEMININITAS DALAM TOKOH DI NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZI - Sayidah Pramitya (TEXTURA, 2021)
AbstractThe purpose of this study is to describe, femininity in the figure of profeminism and counterfeminism in the novel Cinta Suci Zahrana made by Habiburrahman El Shirazy. This research data is profeminism and contrafeminism in the novel Cinta Suci Zahrana created by Habiburrahman El Shirazy. The method used to collect data is read and retrieved a note. Research data collection techniques are (1) reading and understanding the phenomenon of feminism (2) the characters are part of a novel that shows profeminism phenomenon and contrafeminism in the novel by Habiburrahman El Shirazy, Cinta Suci Zahrana; (3) researchers enter and collect data into the research format. Researchers found that the characters of profeminism were Zahrana, Lina, Hasan, Zahrana's parents, Pak Munajat (Zahrana's father), Nuriyah (Zahrana's mother), if we look inside, there are gender prejudices who want to treat women the best, but on the other hand, they still confine women in the "golden cage". And the character of counterfeminism is sir Sukarman, Pak Didik, and the person who sent the SMS to terror. They think they can make a woman fall in love with money and power.Keywords : femininity, characters novel, pro, contra